PENETRATION OF COLONIAL CULTURES IN INDONESIAN HISTORY TEXT BOOKS OF CLASS XI - Faidin, Faidin (JURNAL PENDIDIKAN ILMU SOSIAL, 2017)
This paper is commenced by the writing of study background that essentially explains the identity of the author of the Indonesian History Book, Wardaya. Then, it strives to identify the problems contained in the book. As a result, the word penetration is then chosen as the title. Specifically, penetration is a form of mixing between two different cultures either in good or hasty spheres. Correspondingly, the problem under study is on how is the form of penetration contained in textbooks, on special materials pertaining to the Dutch colonialism to Japan one. They ways they entered Indonesia, the system of government, economy, social politics, and religion were analyzed in the form of penetration in all forms of influence. The theory used in this study was the theory of diffusion that explained also the unification of culture. Therefore, the method used as the support to the writing process is a discourse analysis method developed by Hamad. This theory attempted to see and observe the discourses contained in history textbooks. Therefore, the result of this analysis was in a form of penetration implemented by the Dutch colonial in the fields of culture both in the context of the cultural element and in the context of the livelihoods. This form of penetration in this case was found in the economic field. Moreover, the field of economy can be seen in the colonial trade system. With respect to religions, it more concerned on the way a religion was introduced under Dutch colonialism. Therefore, there was a form of penetration of the influence of Dutch religious values on Indonesian society. Â In regard to the politics, a system of government necessarily forced the native people to obey the colonial government, and in the same time, the rules were made by the colonial. As a result, Indonesian society that has no certain rules were forced to follow the colonial rules such as, in terms of trade, finance, taxation, rent of land. Those aforesaid facts showed that the presence of Western culture had formed a penetration. Hence, it became a proof that indigenous peoples were affected by those penetrations. Therefore, this paper provides a recommendation that penetration should be studied and understood. Also, it can become a comprehensive study in the fields of history and culture.